Knowledge and perception of biosimilars in ambulatory care: a survey among Belgian community pharmacists and physicians - Liese Barbier; Yannick Vandenplas; Steven Simoens; Paul Declerck; Arnold G. Vulto; Isabelle Huys (Journal of Pharmaceutical Policy and Practice, 2021)
Background With the approval of biosimilars for subcutaneously administered products, such as adalimumab, etanercept and insulin, biosimilars become increasingly available in ambulatory care. Little is known about the knowledge and attitudes of healthcare providers who are in charge of dispensing and prescribing biosimilars in this context. This study aims to assess the knowledge and perception about biosimilars among community pharmacists and physicians. Methods Belgian community pharmacists (n = 177) and physicians (n = 30) were surveyed on their knowledge, experience with dispensing/prescribing biologicals including biosimilars, perception regarding interchangeability, switching and substitution and informational and educational needs. Descriptive and statistical analyses were performed. Results Only 32% of community pharmacists and 52% of physicians had yet dispensed/prescribed a biosimilar. Approximately 35% of community pharmacists felt insufficiently trained to counsel patients with biosimilar therapy, which was significantly higher compared to their self-assessed competence to counsel patients with biological therapy in general (p = 0.023). Community pharmacists experienced questions about similarity between reference products and biosimilars (47%) and their interchangeability (42%). Over 40% of physicians found patient uncertainty about efficacy and safety challenging when prescribing biosimilars. A similar proportion of physicians would only prescribe a biosimilar in indications for which the biosimilar has been tested clinically. The majority of pharmacists (58%) was in favor of substitution of biologicals, on the condition that the prescriber would be contacted. Also over 40% of physicians was open to this approach in case of substitution. Educational support, budget for additional staff and transparency about savings were considered suitable stimuli to incentivize biosimilar use. The need for information about biologicals including biosimilars was nearly unanimous among community pharmacists. Also 67% of physicians requested more information. Both community pharmacists and physicians preferred to be informed by their respective professional associations. Conclusions This study showed a substantial need for targeted educational measures to increase the knowledge and confidence about both biological medicines in general and biosimilars in particular among Belgian community pharmacists and physicians. The results may inform educational and policy measures to stimulate biosimilar use in ambulatory care.